Crystal structure of mono-β-alanine hydrochloride - Dmitry S. Tsvetkov; Maxim O. Mazurin (Chimica Techno Acta)
Crystal structure of mono-β-alaninium chloride has been studied by single crystal X-ray diffraction. The compound crystallizes in the orthorhombic system. The space group is Pbca, with the following lattice constants: a = 9.7414(5) Å, b = 7.4671(6) Å, c = 16.5288(11) Å, V = 1202.31(14) Å3, Z = 8. The asymmetric unit contains one β-alaninium cation (+NH3CH2CH2COOH) and one chloride anion. The structure was shown to consist of layers stacked along the c-axis and connected with each other by weak van der Waals forces. Each layer consists of two halves linked by hydrogen bonds between carbonyl and NH3+ groups and, also, between NH3+ groups and Cl- anions. Fourier transform infrared spectrum of β-alaninium chloride was recorded and analyzed. The spectroscopic results were found to support the conclusions of the structural study.